Application of steel slag powder to enhance the low-temperature fracture properties of asphalt mastic and its corresponding mechanism. (20th May 2018) - Li, Qiushi; Qiu, Yanjun; Rahman, Ali; Ding, Haibo
Abstract: This paper aims to study the application of the steel slag powder in asphalt to analyze how it may influence the low-temperature fracture performance of asphalt materials. To fulfill this objective, in this study two different kinds of modified asphalt binders (one is dodecylbenzene sulfonic acid modified asphalt, and another is SBS polymer modified asphalt) were selected, and their behavior after adding steel slag powder was compared with regular limestone powder. Extended bending beam rheometer (Ex-BBR) test and double edge notched tension (DENT) test were employed to characterize low strain rheological and high strain ductile fracture properties of the asphalt binders and asphalt mastics, respectively. The results showed that although dodecylbenzene sulfonic acid (DBSA) modified asphalt and SBS modified asphalt held similar AASHTO M320 regular high-temperature and low-temperature performance grade, their 72hr limiting low-temperature performance grade, and strain tolerance may vary significantly. Moreover, adding 5% larger particle steel slag powder can alleviate the severity of reversible aging due to its higher CaO content than that of limestone powder. As a result, it can absorb more polar components (asphaltene) of asphalt. Apart from this, tougher surface texture and higher specific surface area of larger particle steel slag are also contributing factors in absorbing more asphaltene. Finally, the crack tip opening displacement (CTOD) of two kinds of steel slag powder systems were much higher than that of the limestone powder mastic system under higher temperature and slower loading rate. Graphical abstract: Image Highlights: Application of steel slag powder as substitution of mineral powder. Steel slag powder system had higher fracture resistance than conventional system. Reduction in the reversible aging due to addition of 5% larger particle steel slag powder. Steel slag powder can diminish the severity of low-temperature reversible aging of modified asphalt.